2020
DOI: 10.1136/bmjopen-2019-033850
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autologous osteoperiosteal cylinder and osteochondral graft transplantation in the treatment of large cystic osteochondral lesions of the talus (OLTs): a protocol for a non-inferiority randomised controlled trial

Abstract: IntroductionLarge cystic osteochondral lesions of the talus (OLTs) have been shown to have inferior clinical outcomes after reparative techniques such as bone marrow stimulation. Autologous osteochondral transplantation has been viewed as an alternative choice for treating these lesions, but donor-site morbidity has limited its application. Excellent clinical outcomes have been shown in repairing these types of lesions with autologous osteoperiosteal grafts, and these outcomes are achieved at a low cost and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Autologous osteochondral grafts are usually taken from the osteochondral column of the ipsilateral knee, producing hyaline cartilage with excellent biomechanical properties, but potentially leading to irreversible knee damage. However, iliac bone grafts have fewer complications in the treatment of talar cartilage injuries, and the iliac periosteum has multifunctional stem cells with the ability to differentiate into chondrocytes and fibrocartilage [ 8 , 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous osteochondral grafts are usually taken from the osteochondral column of the ipsilateral knee, producing hyaline cartilage with excellent biomechanical properties, but potentially leading to irreversible knee damage. However, iliac bone grafts have fewer complications in the treatment of talar cartilage injuries, and the iliac periosteum has multifunctional stem cells with the ability to differentiate into chondrocytes and fibrocartilage [ 8 , 9 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteochondral allograft transplantation can also be used, but widespread adoption is unlikely due to its susceptibility to rejection. Periosteal bone grafting was rst proposed as an option for the repair of OCLT by Prof. Qinwei Guo and team and they reported that this procedure had no signi cant disadvantages compared with traditional osteochondral grafting, and satisfactory outcomes were achieved during the 5-year postoperative followup period [17], while similar conclusions were reached by a team in China in a subsequent study.…”
Section: Discussionmentioning
confidence: 57%
“…Osteochondral allograft transplantation can also be used, but widespread adoption is unlikely due to its susceptibility to rejection. Periosteal bone grafting was first proposed as an option for the repair of OCLT by Prof. Qinwei Guo and team and they reported that this procedure had no significant disadvantages compared with traditional osteochondral grafting, and satisfactory outcomes were achieved during the 5-year postoperative follow-up period ( 17 ), while similar conclusions were reached by a team in China in a subsequent study. However, it is considered that there is still a lack of large-scale clinical evidence to support this approach.…”
Section: Discussionmentioning
confidence: 70%